(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This study directed to know the consumer satisfaction towards Patanjali Dant Kanti toothpaste. The fundamental target of to recognize the different factor impacting client in buy of the Patanjali Dant Kanti, to know the consumer satisfaction level about this Patanjali product. The examination configuration utilized as a part of this investigation is spellbinding exploration plan. Information was gathered from 100 example respondents of Rohtak city. Information was gathered through organized poll with five point rating scale questions. Optional information were gathered from the accessible writing sources. For appropriation of poll to the respondents irregular testing strategy was utilized and to gather the respondents feeling, studies was taken among the chosen test respondents. Information was examined utilizing factor examination, rate investigation and chi square technique.